FEATURES OF EMOTIONAL EXPRESSION MENTORS OF PRESCHOOL TEACHERS WITH DIFFERENT LEVELS OF PROFESSIONAL DEFORMATION - Polishchuk, Oksana; Koltunovych, Tetiana (PSYCHOLOGICAL JOURNAL, 2019)
The article analyzes the peculiarities of professional deformations, clarifies the defining characteristic of the concept of "professional deformation of the educator" and outlines the key determinants of professional deformation of educators. It covers also the empirical research of professional deformations among preschool teachers, and their connection with empathy, aggressiveness and behavior in conflict situations. On the basis of the realized theoretical analysis of scientific sources, the definitions of the concept of "professional deformation of the educator" as a set of destructive changes of his personality, determined by the specifics of the activity, the stage of professionalization, objective and subjective factors, were clarified. The key determinants of professional deformities of educators are: conflict, lack of conflict competence, heteroaggression and autoaggression, low level of empathy, unconscious or pragmatic motives for choosing a profession, immunity to innovations, lack of communicative skills, self-reflexive ability and self-relaxation, anxiety, infantilism, pessimism; the contingent (children, parents, colleagues, administration) and the need for effective interaction with everyone; propensity for stereotyping of professional activity and behavior; work with children (contributes to the tendency to simplify, clarify); low prestige of the profession; work experience; feminization of the team; absence of the right to mistake, time for entertainment or rest, permanent staying in a supervising adult with a high level of responsibility for the life and health of the pupils, accompanied by inhibition of their own emotions, states and their manifestations for the well-being of others, personality disorder, violation of the balance "work -privacy". On the basis of the obtained results it was determined that professional deformations of preschool teachers are quite common; educators with a high level of professional deformity are characterized by dissatisfaction with their own professional activities, high rates of autoaggression and heteroaggression, the style of competition used in conflict situation. It was found out that the growth of the level and severity of signs of professional deformation among educators is influenced by the growth of destructive activity in relation to oneself; reducing the ability to jointly choose an alternative option in a conflict situation, increasing the desire to achieve their interests, reducing the level of satisfaction with the content and conditions of their work, aggressive attitude to others. It is assumed that the reduction of autoaggression and heteroaggression, competition in interaction, in particular conflict with other participants in the educational process, increasing job satisfaction, mastering such styles of conflict interaction as a compromise and cooperation of educators with a high level of professional deformation can act as psychological conditions of correction of the professional deformation.